China's development from a global perspective (CAMBRIDGE SCHOLARS PUBLIS, 2017)
For a long time, the idea of China as a culture and society which was voluntarily secluding itself from the rest of the world was dominant. But, in reality, China has always been part of the world, just as the world has always sought to penetrate China. The relationship between China and the world was, in the past, sometimes smooth, and at other times it was difficult, but nevertheless the bond remained alive. This collection presents an analysis of China from a global perspective within a broad temporal and spatial spectrum. It reveals the early relations established between the Roman Empire a.